2017
DOI: 10.1002/bies.201700167
|View full text |Cite
|
Sign up to set email alerts
|

Soft‐Bodied Fossils Are Not Simply Rotten Carcasses – Toward a Holistic Understanding of Exceptional Fossil Preservation

Abstract: Exceptionally preserved fossils are the product of complex interplays of biological and geological processes including burial, autolysis and microbial decay, authigenic mineralization, diagenesis, metamorphism, and finally weathering and exhumation. Determining which tissues are preserved and how biases affect their preservation pathways is important for interpreting fossils in phylogenetic, ecological, and evolutionary frameworks. Although laboratory decay experiments reveal important aspects of fossilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 119 publications
1
76
0
Order By: Relevance
“…The contact between the lateral outer sheaths of neighboring tentacles exhibits a kink with some relief (Figures 2E and 2F). The outer sheaths appear as dark shadows in the mCT scans, indicating low density and most likely an organic composition, corroborated by their dark coloration, perhaps due to melanin or another recalcitrant pigment [47][48][49].…”
Section: Descriptionmentioning
confidence: 99%
“…The contact between the lateral outer sheaths of neighboring tentacles exhibits a kink with some relief (Figures 2E and 2F). The outer sheaths appear as dark shadows in the mCT scans, indicating low density and most likely an organic composition, corroborated by their dark coloration, perhaps due to melanin or another recalcitrant pigment [47][48][49].…”
Section: Descriptionmentioning
confidence: 99%
“…The likely BST recently described as the Qingjiang Biota, also from the Cambrian of China, preserves exquisite, abundant and diverse cnidarians (Fu et al, 2019). It is clear that decay sequence is not everything when it comes to fossil preservation merely informing on preservation potential of certain characters (Parry et al, 2018). Even with characters as unlikely to survive as anthozoan polyp tentacles, you still sometimes win the fossilisation lottery.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…To date, non-iridescent structural colour has not been investigated in the fossil record. It has been shown that keratin degrades during the process of fossilization [15,16]. Hence, the reliability of reconstructing non-iridescent structural colours, which are generated by keratin nanocavities in feather barbs would be impossible.…”
Section: Introductionmentioning
confidence: 99%